Tolerability of Flexible and Rigid Cystoscopy during DJ Stent Removal in Women (Nepal Medical College Journal, 2025)
Cystoscopy is routinely done in urological practice. It may be for diagnostic or therapeutic purpose. Generally, it is done to rule of urethra and bladder pathology. Many of time cystoscopy is performed under local anesthesia, however sometime patient need spinal or general anesthesia. DJ stent is another surgery which is routinely practiced after many endourological as well as open surgery in Urology. It is general practice to remove DJ stent within 6 weeks to 3months but this duration may vary on type of surgery, need of DJ stent and development of complications like lower urinary tract symptoms(LUTs) due to DJ stent. Cystoscopy is done to remove all DJ stent. Its surgeon’s choice to remove DJ stent with either rigid cystoscopy or flexible cystoscopy. This observational study was conducted in Nepal Medical College Teaching Hospital with objective to evaluate the tolerability of flexible versus rigid cystoscopy in women during DJ stent removal and to find out the pain (VAS SCORE); intraoperative, post-operative and need for analgesia following Cystoscopy. Total 64 patients fulfilling the inclusion criteria were included and were randomly divided into 2 groups i.e. group A and group B. Storz 18 Fr flexible cystoscopy was used for group A and 18 Fr rigid cystoscopy was used for group B. Cystoscopy was done in both group, DJ stent was identified and removed. VAS score was calculated during and after the procedure. Mean age for group A was 40.84 years and group B was 36.8 years. VAS score intraoperative for group A was 3.7±1.4 and for group B was 6.1±0.7. Postoperative VAS score for group A was 2.4±1.2 and group B was 5.3±0.7, VAS showing P value